Education in health, prevention and management of back pain under the approach "integration school community from the area of Physical Education"/Educación en salud, prevención y manejo del dolor de espalda bajo el enfoque "integración escuela comunidad d - Efrén Mesías Palacios Zumba; Richar Jacobo Posso Pacheco; Laura Cristina Barba Miranda; Bertha Susana Paz Viteri (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The purpose of the study was to assess the scope of an action plan for health education, prevention and management of back pain, with the School Community Integration approach from the Physical Education Area in the empowerment of knowledge and its application in favor of a comprehensive health to members of an educational institution in the city of Quito; it had as a methodological approach the socio-critical paradigm, according to the participatory action research method. Representatives of children enrolled in said institution are included as study subjects. The study was carried out in three stages. 1- Participatory diagnosis, where back pain appears as a frequent condition. 2- Preventive program that integrates anatomical, biomechanical, postural hygiene and exercise knowledge. 3- Evaluation of knowledge and skills acquired. Clinical history and determination of risk factors, application of pre and post-test related to back care, posture and exercises were performed. Based on the scores obtained and the observation of acquired skills, it is determined that the action plan allowed the acquisition of cognitive, behavioral and procedural values in all participants. The Community School Integration approach from the Physical Education Area is considered as a viable program of execution by the Ecuadorian Ministry of Education. These elements contribute to the maintenance, promotion and prevention of health conditions of community members.